2011
DOI: 10.1590/s1516-14392011005000073
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of strontium up to 5 Mol. (%) to hydroxyapatite did not affect its cytocompatibility

Abstract: The aim of this work was to produce hydroxyapatite (HA) granules containing 0, 0.5, 1 and 5 mol. (%) of strontium (Sr), evaluate the physico-chemical properties and also the cytotoxicity by three different parameters of cell viability (ISO 10993-5, 10993-12). The physico-chemical characterization was carried out by using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR) and X-ray fluorescence (XRF). The XRD profile presented the main peaks of HA (JCPDS 860740) and the absorption bands of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 30 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…However, Chung and Long [206] proved that coatings with a concentration exceeding 38.9 at.% of Sr significantly inhibit RAW264.7 osteoclast differentiation. Dos Santos Tavares et al [218] revealed that hydroxyapatite containing from 0.5 to 5 mol.% of Sr did not affect dehydrogenase activity, membrane integrity or DNA content.…”
Section: ϰ͘ϯ͘ϯ͘ ^ƚƌžŷƚŝƶŵmentioning
confidence: 97%
“…However, Chung and Long [206] proved that coatings with a concentration exceeding 38.9 at.% of Sr significantly inhibit RAW264.7 osteoclast differentiation. Dos Santos Tavares et al [218] revealed that hydroxyapatite containing from 0.5 to 5 mol.% of Sr did not affect dehydrogenase activity, membrane integrity or DNA content.…”
Section: ϰ͘ϯ͘ϯ͘ ^ƚƌžŷƚŝƶŵmentioning
confidence: 97%
“…SrHAP2, [24,25] and the transformation of HAP to β-TCP (tricalcium phosphate) above 700 °C. [26,27] The to pure HAP based on statistical calculation (F and t probes).…”
Section: Sr-doped Hapsmentioning
confidence: 99%
“…presents that the Ca/P or (Ca+Sr)/P molar ratios are approximately 1.67 in the case of HAPht and SrHAP4 but only 1.42 for SrHAP2. This small ratio would mean the formation of Ca-deficient HAP which decomposes above 700 °C to β-TCP[26,27,32]. As the samples were pure HAP without any other phases, we assume the real value is close to the theoretical 1.67.…”
mentioning
confidence: 97%
“…Such phenomenon has been reported in both Sr based drug [20] and Sr doped ceramics [14], although the optimum content of Sr may be different as reported in different doped materials. As reported by Tavares et al, Sr doping at 5 mol% has no cytotoxicity on osteoblasts [21]. In the work of Fu et al, Sr substituted HA containing different Sr concentrations (0%, 1%, 5%, 10%, 100%) have been biologically tested [22,23].…”
Section: Discussionmentioning
confidence: 99%